Therapeutic Reality Counseling, WDEP Counseling And Resilience Of Adolescents With Premarital Free Sex Dependence: A Literature Review - Aditama, Mint Husen; Ramli, M. (Universitas Mercu Buana Yogyakarta, 2023)
Counseling reality therapy, counseling and resilience are forms of providing assistance that is individual or group in the counseling process. Generally, reality counseling and WDEP are used to change behavior now. The reality of this therapy is focused on confronting the counselor by facing reality and helping to get the needs without harming oneself and others. Meanwhile, WDEP is more focused on meeting the needs of counselors so as not to deny the existing reality. How are these two counselings interconnected and create the strength to overcome adolescent resilience with premarital promiscuous sex dependence?This article reviews with an epistemological point of view from a literature review of WDEP counseling and the reality of therapy from early 2013 to late 2022 to find out its use in overcoming adolescent resilience with premarital free sex dependence.Â To achieve this goal, three steps followed: (1) prepare a search strategy for systematic literature review and gather representative paper research into the use of WDEP counseling and therapeutic reality using the Google Scholar and Scient Direct digital literature search engines; (2) store search results into a mandeley database to synthesize literature reviews; (3) organize literature review and extract data into qualitative and quantitative information on WDEP counseling and Reality therapy on the resilience of adolescents with premarital free sex dependence.Â The authors propose a taxonomy of literature through interpretive analysis: (1) time analysis to determine the causes of trends in the use of WDEP counseling and the reality of therapy in the last ten years; (2) terminology analysis to examine the development of the application of WDEP counseling and the reality of trerapi; (3) analysis of the use of WDEP counseling and the reality of the counselor on the nature and characteristics of counseling; (4) analysis of WDEP counseling and the reality of trerapi on counselor's perceptions; (5) analysis of the use of WDEP counseling and the reality of trerapi in relation to socio-cultural, family, or personal rules; (6) analysis of WDEP counseling and trerapi reality of self-concept, self-esteem and resilience of adolescents with premarital free sex dependence.